An Analysis of Teachers’ Strategies in Teaching Reading Comprehension at Grade Seventh of SMPN 25 Pekanbaru - Bella Angelina; Syofianis Ismail (CV. ULIL ALBAB CORP, 2023)
This research aimed to determine English teachers' strategies in teaching reading comprehension to seventh-grade students in junior high school. This research was designed as descriptive qualitative research. The research participants were two English teachers who teach in the seventh grade of the school. Each English teacher had two meetings, during which the researcher observed them. The research instruments were observation and interview. The instruments were used to determine the teachers' strategies for teaching reading comprehension. The data results were analyzed and broken down into three stages: Data reduction, Data Display, and Concluding. The result showed that Teacher A used Question Answer Relationship Strategy (QAR), and Teacher B used a Graphic Organizer Strategy. Both teachers applied strategies that were very effective in teaching reading comprehension in that school. The students’ motivation proved it, as did their attention and the teachers’ ease in the teaching and learning process.